1998
DOI: 10.1111/j.1834-7819.1998.tb00143.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of bond strengths of denture repair resins by a torsional method

Abstract: Ab stractChemical cure resin materia.ls are generally used in the repair of dentures. Different repair resins used may yield different results. The bond strength of three autopolymerizing resins were evaluated using a torsional test method. The results showed that Palapress and Caulk resins had a higher repair strength than Rapid Repair resin .Key words: Denture repair resins, bond strength, torsion tests evaluation.(Received for publication March 1995. Revised June 1995. Accepted July 1995 Int roductionAlth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…The shear components are observed to remain in 50 MPa range. In various studies, it is indicated that the debonding stresses at the tooth -denture interface are at the orders of 10-40 MPa in quasi-static environment in shear (in contact local tangent plane) (Thean et al 1996;Thean et al 1998;Mian et al 2013), and 27-69 MPa in tensile (normal to interface) directions (Amin 2002;Alsiyabi et al 2004;Amarnath et al 2011). These values indicated are much lower than the ones calculated here; however, it should be noted that the tests referenced therein are conducted in quasi-static conditions: Under such conditions, PMMA is much softer and yields more easily compared with its high-strain-rate behavior.…”
Section: Discussionmentioning
confidence: 97%
“…The shear components are observed to remain in 50 MPa range. In various studies, it is indicated that the debonding stresses at the tooth -denture interface are at the orders of 10-40 MPa in quasi-static environment in shear (in contact local tangent plane) (Thean et al 1996;Thean et al 1998;Mian et al 2013), and 27-69 MPa in tensile (normal to interface) directions (Amin 2002;Alsiyabi et al 2004;Amarnath et al 2011). These values indicated are much lower than the ones calculated here; however, it should be noted that the tests referenced therein are conducted in quasi-static conditions: Under such conditions, PMMA is much softer and yields more easily compared with its high-strain-rate behavior.…”
Section: Discussionmentioning
confidence: 97%
“…According to Beyli and von Fraunhofer, 57 the use of a maximum of 3-mm gap size decreased the degree of polymerization contraction and reduced any color difference between the denture base and repair material. In addition, if the interface is wider than 3 mm, pure cohesive fracture might occur instead of mixed fracture; 22 however, this behavior was not observed in a study by Rached et al,24 who showed that the repair methods exhibited a low incidence of purely adhesive rather than cohesive failures.…”
Section: Mechanical Treatmentmentioning
confidence: 93%
“…The torsion specimen also has a uniform state of stress at any point on the specimen surface, and this state of stress is less dependent on parallelism and specimen shape than in the three-point bending test. 22 Controversies relating to the effect of surface treatment of the acrylic resin have arisen as a result of research employing different test methods (Table 1). Hence, the standardization of test methods and the conversion of results according to International Unit System for denture repairs studies are required.…”
Section: Test Methods For Denture Repairsmentioning
confidence: 99%
See 1 more Smart Citation
“…19-31 특히, 레진 의치상 수리에 주로 사용되는 자가중합레진의 강도는 열중합레진의 18-81%에 불과하다는 연구결과가 보고되었기 때문에, [20][21][22][23][24][25][26][27] 추가적으로 금속이나 섬유(fiber)와 같은 보강재가 사용되어 왔다. 금속보강재는 비교적 술식이 간단하고 저렴하기 때문에 의 치상 강화에 널리 사용된다.…”
Section: 된다unclassified